(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2012)
A wide variety of applications require reliable and secure verification schemes to confirm the identity of an individual requesting authorized accessing to a specified service. Examples of such applications include secure access to buildings, personal computer systems, laptops, cellular phones and ATMs. In the absence of robust verification schemes, these systems are subject to the tricks of an impostor. Biometric authentication (BA) is a problem of verifying an identity claim using a person’s behavioral and physiological characteristics.